Canva & Wordwall Digital Media Development at Religious Learning TPQ Al Irsyad Graha Asri Week Saturday in Bengkulu City - Desy Eka Citra Dewi; Rahma Dwi Miftakhia; Pradita Ayu Nurwana; Lisa Apriani; Yeni Puspita Sari (Edumaspul: Jurnal Pendidikan, 2026)
Religious learning at TPQ Al Irsyad Graha Asri Pekan Sabtu, Bengkulu City, has so far relied on conventional methods based on verbalistic lectures and static textbooks, thus triggering student boredom and low retention of Islamic religious material. This Thematic Community Service (KKN) activity based on Research by the PGMI Study Program Group 12 aims to transform the conventional religious learning model into an interactive one through the integration of the Canva and Wordwall digital platforms. The implementation method uses the Asset-Based Community Development (ABCD) approach which includes the stages of Discovery, Dream, Design, and Destiny. The results of the service show a significant increase in educators’ technological literacy, the visual quality of teaching materials through Canva, and student activeness in interactive evaluations based on Wordwall gamification. Measurement using the Societal Impact Index (SII) confirmed a partner satisfaction level of 91.4% (very high). The resulting social impacts include the growth of an adaptive digital religious ecosystem, a radical increase in student learning motivation, and the development of institutional independence in managing technology-based learning in Pekan Sabtu, Bengkulu City. Abstrak Pembelajaran keagamaan di TPQ Al Irsyad Graha Asri Pekan Sabtu Kota Bengkulu selama ini masih mengandalkan metode konvensional berbasis ceramah verbalistis dan buku teks statis, sehingga memicu kejenuhan santri serta rendahnya retensi materi keagamaan Islam. Kegiatan pengabdian masyarakat (KKN) Tematik berbasis Riset Prodi PGMI Kelompok 12 ini bertujuan untuk mentransformasi model pembelajaran keagamaan konvensional menjadi interaktif melalui integrasi platform digital Canva dan Wordwall. Metode pelaksanaan menggunakan pendekatan Asset-Based Community Development (ABCD) yang meliputi tahapan Discovery, Dream, Design, dan Destiny. Hasil pengabdian menunjukkan adanya peningkatan signifikan dalam literasi teknologi pendidik, kualitas visual materi ajar melalui Canva, serta keaktifan santri dalam evaluasi interaktif berbasis gamifikasi Wordwall. Pengukuran menggunakan Societal Impact Index (SII) mengonfirmasi tingkat kepuasan mitra sebesar 91,4% (sangat tinggi). Dampak sosial yang dihasilkan mencakup tumbuhnya ekosistem digital keagamaan yang adaptif, peningkatan motivasi belajar santri secara radikal, serta terbangunnya kemandirian institusional dalam pengelolaan pembelajaran berbasis teknologi di Pekan Sabtu Kota Bengkulu.